Ultrasound Imaging of Head/Neck Muscles and Their Fasciae: An Observational Study - Pirri, Carmelo; Fede, Caterina; Fan, Chenglei; Guidolin, Diego; Macchi, Veronica; De Caro, Raffaele; Stecco, Carla (Frontiers in Rehabilitation Sciences, 2021)
Background: Masticatory muscle thickness provides objective measurements of the temporo-mandibular motor function, which may change in patients with oral myofascial pain. Moreover, they are considered as being part of the cranio-cervical unit by crucial relationship with cervical muscles and their fasciae. In this study, we aimed to assess by an ultrasound (US) imaging the fasciae of the masseter, temporal and sternocleidomastoid muscles to understand their mean thickness and eventual variation in relationship with the muscles, side, sex. Methods: We studied 16 healthy volunteers without tempo-mandibular joint dysfunction. Concerning each subject were evaluated the range of motion of the temporo-mandibular joint and of the neck, the thickness of muscles and their fasciae of both sides and the delta of muscle thickness. Results: all the motor evaluations of the subjects showed normal ranges. The US results showed that the fasciae have a mean thickness of 0.50 ± 0.1 mm, which did not change during muscle contraction. The evaluated muscles presented a symmetry between right and left (p>0.05), even if the delta of muscle (US) thickness had a huge range between different subjects, for example in the masseter muscle from 0.7 mm to 4.2 mm. Conclusions: Ultrasound imaging is a suitable and reliable tool to study the muscles and fasciae of the head and neck region, permitting also the evaluation of the ability of the muscles to contract. Finally, identifying functional asymmetry that could become symptomatic, US imaging could allow an early rehabilitation treatment.